Benchmarking the implementation of Private Finance Initiative (PFI) in Malaysia - Siti Suhana binti Alias (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Private Finance Initiative (PFI) is a partnership between the public sector and the private sector that takes advantage of private resources and expertise particularly in the provisioning of public infrastructure and services projects. In Malaysia, PFI was formally introduced under the Ninth Malaysia Plan (2006-2010) as an alternative procurement methodand by 2010; the practice was reformed under the new wave of Public Private Partnership (PPP). Current practice has developed distinctive features however whether the Malaysian PFI is in line with the global implementation of PFI is unknown as studies relating to it are scarce. This is evident as the practice of PFI in Malaysia is still considered in the early development stage compared to other PFI implementing countries. This dissertation therefore brings attention towards the implementation of PFI in Malaysia through the process of benchmarking whereby the Malaysian PFI features is compared against an appropriate standard of measurement comprising eight benchmarked PFI features such as responsibility of the parties involved, right of asset ownership, output specification, legal and regulatory framework, Value for Money (VFM), payment due to the private sector, Special Purpose Vehicle (SPV) and risk allocation. Methods used for collecting data include literature review, content analysis and questionnaire survey. The survey was conducted in order to collect responses on the comparison of PFI features from the perspective of the public sector as well as the private sector. Findings indicated that the Malaysian practice of PFI is considered to be similar to the benchmark.